Data wrangling in R - Magle, C. Tobin, speaker (Colorado State University. Libraries, 2017)
What you can do with your data depends strongly on how its formatted. This month's coding and cookies will cover how to manipulate datasets using an R package called dplyr. After this session, you will be able to subset, reformat and summarize your data. A basic working knowledge of R and R studio would be helpful for you to get the most out of this session.
Coding and cookies
ZIP file contains: instructional materials.
Accessibility features: Transcript.
Keywords: data management; data education; Data editing; Programming languages (Electronic computers)